Transmission of Psychological Trauma Through Literature: Ömer Seyfettin and the White Tulip - Özgüç, Anıl; Oral, Gökhan (The Bulletin of Legal Medicine, 2019)
Ömer Seyfettin (1884-1920) wrote the "White Tulip" story in 1912. As in almost all the stories of the author, the “White Tulip” carries the traces of the social and political structure of its period. The story is about the massacre of the Turkish people living in Serres after the Balkan Wars by Bulgarian Commander Radko. The Bulgarian gangs tortured and killed their Turkish villagers without discrimination between women and children and they plunder their houses. They destroyed their mosques or converted them into a church. White Tulip, who is described as the most beautiful girl in Serres and named for the story, is subjected to rape attempts of Commander Radko. White Tulip commits suicide in order not to allow it. However, the victim’s suicide does not stop the Commander Radko and he rapes the dead body of the White Tulip. The story contains certain concepts and circumstances to be evaluated within the scope of forensic sciences such as occupation, massacre, plunder, torture, rape, suicide and finally rape of a person’s dead body. The aim of this study was to evaluate the concepts and deviations of the forensic sciences in terms of the fiction of the story and the life of the writer Ömer Seyfettin and also to discuss the place of the works of Ömer Seyfettin’s children literature and transmission of psychological trauma through literature.